The Power of Thermosonication on Quality Preservation and Listeria Control of Blueberry Juice - Eleonora Panaro; Teresa R. S. Brandão; Cristina L. M. Silva; Fátima A. Miller (Foods)
Due to the increasing consumer demand for healthy, beneficial foods, natural fruit juices have gained popularity for their rich nutritional value and appealing flavor. However, traditional thermal processing can compromise these quality attributes. This study investigates using pulsed thermosonication, a novel mild thermal processing method, on Listeria innocua inactivation in blueberry juice, chosen for its high phenolic and anthocyanin content. Ultrasonication was applied at 60% and 100% amplitudes combined with heat treatments at 45 °C and 55 °C and compared to control heat treatments. The Weibull model effectively described the inactivation kinetics, showing that the thermosonicated samples required significantly shorter times (1 and 25 min) for a 5-log reduction compared to the heated samples (10 and 60 min). While pH, total soluble solids, and water activity remained unaffected, color parameters improved, and the best retention of phenolics and anthocyanins was observed at 100% amplitude and 45 °C. Rheological properties were unchanged. The findings demonstrate that thermosonication at milder temperatures is more effective than conventional heat treatment for microbial inactivation and quality retention in blueberry juice, suggesting it is a superior processing method for preserving fruit juices’ nutritional and sensory attributes.